2011
DOI: 10.1016/j.resmic.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bacteria on diatom community structure – the ‘antibiotics’ approach

Abstract: To investigate the effect of bacteria on diatoms at the community level, sediment samples from an intertidal tropical environment were treated with penicillin (a β-lactam antibiotic that can affect diatoms only through bacteria). Streptomycin (an aminoglycoside) and chloramphenicol, antibiotics that can potentially affect protein synthesis in diatom organelles and photosynthesis, were also used for comparison. The changes in diatom community structure and the resistant and tolerant bacterial fractions were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
7
2
Order By: Relevance
“…Overall, in the present work, streptomycin and chloramphenicol did not inhibit bacteria. These observations differ from those in similar experiments by D'Costa & Anil () on benthic diatom communities. In the latter study, streptomycin and chloramphenicol inhibited bacteria to <10 and 77% of control values, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, in the present work, streptomycin and chloramphenicol did not inhibit bacteria. These observations differ from those in similar experiments by D'Costa & Anil () on benthic diatom communities. In the latter study, streptomycin and chloramphenicol inhibited bacteria to <10 and 77% of control values, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…5M6) and one diatom strain ( C. closterium ). Bacteria and diatoms are very close in fouling biofilms [ 44 ], and they might support each other by exchange of chemical cues [ 45 ]. The mixed biofilm, constituted of bacteria and diatoms in symbiotic relation, can establish a resistant consortium against AF agents.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the interaction between diatoms and bacteria in biofilm might be regulated by a complex network of chemical factors including EPS and other substances (Khandeparker et al, 2014). For example, bacteria influenced the diatom community structure by antibiotic-mediated interactions (D'Costa and Anil, 2011). Recently, Windler et al (2015) reported that the bacteria Bacteroidetes strain 32 influenced the biofilm structure and biomass of the diatom Achnanthidium minutissimum and pointed out that little was know about the chemical interactions between diatoms and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between diatoms and bacteria are very close in fouling biofilms. In addition to being symbiotic or antagonistic, diatoms and bacteria might support each other through cross-feeding, possibly optimize by exchange of chemical cues (D'Costa and Anil, 2011). It was reported that bacteria influenced the growth and metabolic activities of diatoms, such as EPS production, capsule formation and adhesion strength of diatom cells (WigglesworthCooksey and Cooksey, 2005).…”
Section: Introductionmentioning
confidence: 99%